Memes in Journalistic Texts about the Pandemic and War: Frequency and Strategies of Use - Zhuravska, Oksana (Roczniki Nauk Społecznych, 2024)
This study aimed to determine whether memes in journalistic materials increased during such prolonged crises as the pandemic and the full-scale Russian invasion of Ukraine. A content analysis of Polish media outlets Fakt, WP Wiadomości, Wyborcza, Rzeczpospolita, and the Ukrainian outlet Suspilne from December 2019 to April 2024 helped identify 1,271 articles featuring memes and examine the strategies for using memes in these articles. The topic of the war is dominant in Suspilne and Rzeczpospolita. The pandemic topic is not dominant in any of the analyzed media. Approximately every 50th article with memes covers the pandemic, and every 15th article covers the war. Visualization is not the leading strategy for using memes in articles, except Fakt. Instead, descriptions of the memes themselves and their use as literary devices, i.e. verbal strategies, predominate. Although rare, media outlets do publish digests that incorporate memes on pandemic and war topics.